2021
DOI: 10.1002/aoc.6173
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization, and density functional theory calculations of the two new Zn (II) complexes as antibacterial and anticancer agents with a neutral flexible tetradentate pyrazole‐based ligand

Abstract: Two new mono‐ and dinuclear zinc (II) complexes with a formula of [Zn (LN)OMeCl] (1) and [Zn2(LN)(N3)2Cl2] (2) [where LN = 1,1,3,3‐tetrakis(3,5‐dimethyl‐1‐pyrazolyl)propane)] have been synthesized in methanol as a solvent and fully characterized by the single crystal X‐ray diffraction, elemental analysis, FT‐IR, UV–Vis, density functional theory (DFT) calculations, antibacterial, and anticancer properties. In both of them, zinc ion is tetrahedrally coordinated to two nitrogen atoms from one of the chelating bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…According to DFT calculations, Beheshti et al reported the synthesis of a pyrazolyl-based mononuclear zinc(II) complex with a 4.59 eV HOMO-LUMO energy gap. 37 The HOMO-LUMO energy gap value of the zinc(II) complex based on the benzoyl hydrazone ligand was calculated by the DFT method to be 3.76 eV in 2017. 38 As a result, the synthesized zinc(II) complex in this study is less stable than those that have been previously described.…”
Section: Dft Studiesmentioning
confidence: 99%
“…According to DFT calculations, Beheshti et al reported the synthesis of a pyrazolyl-based mononuclear zinc(II) complex with a 4.59 eV HOMO-LUMO energy gap. 37 The HOMO-LUMO energy gap value of the zinc(II) complex based on the benzoyl hydrazone ligand was calculated by the DFT method to be 3.76 eV in 2017. 38 As a result, the synthesized zinc(II) complex in this study is less stable than those that have been previously described.…”
Section: Dft Studiesmentioning
confidence: 99%
“…Recently, various coordination polymers (CPs), metal organic frameworks (MOFs), and covalent organic frameworks (COFs) have been reported as new candidates for the removal of iodine. ,, In the structure of these polymers, the nature of metals, kind of ligands, counterions, type of solvents, and reaction conditions play a vital role. Alternatively, there is a rapid growth in the manufacturing of the ligands with O, N, and S donor atoms to use in the CPs and MOFs. In particular, the systematic designs of sulfur-containing ligands have been investigated in bioinorganic chemistry and for their ability to create various coordination network architectures. , Following our ongoing research on the development of coordination polymers with S donor ligands, ,, herein, we report four novel metal–organic frameworks with d 10 transition metals of group 12 and L s (pbit) ligand [where L s or pbit = 1,1′-(pentane-1,5-diyl)­bis­(-3-methyl-1 H -imidazole-2-thione)]. The title polymers were applied as an adsorbent for hydrogen sulfide and also used for iodine removal.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, macrocyclic Schiff bases are particularly important in macrocyclic chemistry because of their exible synthesis, their selectivity, and even their ability to stabilize many metals in various oxidation states [12][13][14][15][16]. However, a huge number of tetraaza macrocyclic (N 4 ) metal complexes show interesting biological activities such as antifungal [17,18], antibacterial [19][20][21], antimicrobial [22][23][24][25] and anticancer [11,26,27] effects.…”
Section: Introductionmentioning
confidence: 99%